Sistem Kontrol dan Monitoring Level dan Flow Tangki Sirkulasi Berbasis ESP8266 - Gultom, Golfrid; Azis Rahmansyah, Abdul; Irfian Situngkir, Dejoi (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2025)
Fluid circulation system is a process that is often carried out in wastewater treatment, chemical industry processes or feed water for boilers. Controlling and monitoring the flow and level of fluid in the circulation system is very vital in a process, especially in the chemical industry process. The Internet of things using the ESP8266 device can be utilized for the effectiveness and efficiency of control and monitoring. In this study, flow sensors and level sensors are combined into a flow and level control model in a fluid circulation system with circulation between 2 tanks. The accuracy of tank level measurement is 97.05% when compared between actual measurements and measurements on wirelessly connected devices. The actuator response in the circulation system is the main part that will be modeled and built on wireless applications and a fairly reliable response is obtained even though there is an average response delay of 1.28 seconds. From the results of the research that was developed, it has been able to become a level and flow control and monitoring system using the ESP 8266 device as part of the control and monitoring system developed in the industrial 4.0 scheme.